The Influence of Economic Value Added (EVA), Market Value Added (MVA) And Company Value On Stock Prices PT. Bank Panin Dubai Syariah - Al Rafi, Fauzan; Samsul, Samsul; Hamid, Supriadi (Jurnal Hukum Ekonomi Syariah : AICONOMIA, 2024)
Share price is an indicator of the success of running a company. When a company's share price rises, investors believe the company is successful in managing its business. If share prices continue to fall, it means the company has not succeeded in increasing its company value. This research aims to determine the influence of each variable Economic Value Added (EVA), Market Value Added (MVA), and Company Value on the share price of PT. Bank Panin Dubai Syariah both partially and simultaneously. This research is quantitative research with a correlational approach (correlation), the research data source is secondary data in the form of financial reports and share prices of the company PT. Bank Panin Dubai Syariah quarter 2014-2021. Data hypothesis testing in this study uses multiple linear regression tests. Data analysis includes classical assumption tests, multiple regression analysis, F tests and T tests. The results of the research reveal that the Economic Value Added (EVA) variable has a significant and negative effect on stock prices, EVA produces value negative, indicating that the company's performance and ability to generate wealth have not been achieved for the company and investors. The Market Value Added (MVA) variable has no significant and negative effect on stock prices. MVA produces a negative value which indicates that the company's main goal of increasing shareholder wealth has not been achieved. Meanwhile, the company value variable (PBV) produces a significant and positive value which indicates the share price is below 1, which means the share price is undervalued or relatively cheap.